HUBUNGAN KONDISI SANITASI LINGKUNGAN RUMAH TANGGA DENGAN KEBERADAAN JENTIK VEKTOR DENGUE DI DAERAH RAWAN DEMAM BERDARAH DENGUE KOTA DUMAI TAHUN 2008 - Zulkarnaini Zulkarnaini; Yusni Ikhwan Siregar; Dameria Dameria (Program Pascasarjana Universitas Riau, 2009)
Dumai is area endemic of Dengue disease (DBD) with condition of environmental sanitary ingeneral has not well. Purpose of this research is to know image of condition of environmentalsanitary in Kota Dumai and sees are there the relation of condition of household area sanitarywith existence larvae of vector dengue and area sanitary aspect what which most dominantrelated to existence larvae of vector dengue in disease gristle area of Kota Dumai. This researchis research type of observasional with planning